A bibliometric review of evergreening loans literature: An analysis of scopus-indexed publications - Mohammad Q. M. Momani (Discover Sustainability)
Abstract This paper employs a comprehensive bibliometric approach to analyse the growth trajectory, publication patterns, journals, global author distribution, scientific output, and thematic focus within the field of evergreening loans. A total of 816 publications from the Scopus database, spanning 1983 to 2023, were carefully analysed to reach insightful results. To aid the analysis, I utilized VOSviewer software, which enabled performance analysis and scientific mapping. The results show a strong academic interest in evergreening loans. The US emerges as the dominant country in both publication volume and citation counts, followed by Germany, the UK, and Italy. It also identifies the most influential journals in the field, with key themes focusing on governance, debt restructuring, and financial stability. Despite the various emerging research trends in the field, several research gaps persist. Notably, interdisciplinary studies combining economics, finance, policy, and legal perspectives remain limited. Additionally, while scholars acknowledge firms' negotiations during financial distress, little is known about the behavioral factors influencing decision-making in evergreening loans. Understanding these behaviors could explain the persistence of these practices. Furthermore, there is a lack of comparative studies on the debt restructuring strategies adopted by different countries and the effectiveness of their policies in ensuring economic and financial stability. This is the first study to provide a comprehensive bibliometric analysis of the evergreening loans literature, offering unique insights into key themes, influential countries, and emerging research trends, and contributes to advancing both theoretical understanding and practical applications, with implications for future interdisciplinary research.